2007
DOI: 10.1021/jf0630926
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in Marine Organisms from the Gulf of Naples, Tyrrhenian Sea

Abstract: Polycyclic aromatic hydrocarbons (PAHs) were determined by an HPLC method with fluorescence detection in bivalves (Mitylus galloprovincialis), cephalopods (Todarodes sagittatus), crustaceans (Aristeus antennatus), and fish (Mullus surmeletus, Scomber scombrus, Micromesistius poutassou, and Merluccius merluccius) caught in the Gulf of Naples (Tyrrhenian Sea, Italy). Anthracene, fluoranthene, pyrene, benz(a)anthracene, chrysene, benzo(b)fluoranthene, and benzo(k)fluoranthene were detected, at different concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 23 publications
2
25
0
1
Order By: Relevance
“…A similar trend, with high predominance of threeand four-ring PAH, was also reported by Binelli and Provini (2003), and by Perugini et al (2007) in some species of bivalves. The total PAH concentrations in mussels, clams, and cockles were comparable with those reported for moderately contaminated areas (200-1,000 ng/g) of different bays worldwide (Baumard et al 1999;Chase et al 2001;Liu and Kueh 2005), and at least one order of magnitude lower than in highly anthropogenically impacted sites (Telli-Karakoç et al 2002;Liu and Kueh 2005).…”
Section: Pah and Their Origin In Sedimentssupporting
confidence: 85%
“…A similar trend, with high predominance of threeand four-ring PAH, was also reported by Binelli and Provini (2003), and by Perugini et al (2007) in some species of bivalves. The total PAH concentrations in mussels, clams, and cockles were comparable with those reported for moderately contaminated areas (200-1,000 ng/g) of different bays worldwide (Baumard et al 1999;Chase et al 2001;Liu and Kueh 2005), and at least one order of magnitude lower than in highly anthropogenically impacted sites (Telli-Karakoç et al 2002;Liu and Kueh 2005).…”
Section: Pah and Their Origin In Sedimentssupporting
confidence: 85%
“…They observed that 72% of mussels had the highest PAH levels of 45-207 μg/kg (fresh weight). In addition, the maximum levels of heavier PAHs (BAP, DBA, and BPY) in mussels were also detected particularly during the winter (December) owing to the inflow of marine and ground water (Perugini et al, 2007). However, at the same time, the fish were not contaminated with heavier PAHs in that period.…”
Section: Water-based Food Productsmentioning
confidence: 93%
“…Perugini et al (2007) observed that the concentration levels of several PAHs (ANT, FLT, PYR, BAA, CHY, BBF, and BKF) vary considerably between different seafoods (e.g., cephalopods (squid), crustaceans (shrimps), mussels, and fish) collected from the Gulf of Naples (depth of 30-60 cm). They observed that 72% of mussels had the highest PAH levels of 45-207 μg/kg (fresh weight).…”
Section: Water-based Food Productsmentioning
confidence: 99%
“…Therefore, there is a strong demand for simple, rapid and sensitive methods that allow evaluating and monitoring PAH in environmental water samples at trace level. For such purpose, different analytical techniques have been employed like gas chromatography coupled with time-of-flight mass spectrometry (GC-TOF-MS) [7], flow injection capillary electrophoresis [8], high-performance liquid chromatography (HPLC) with UV-vis and fluorescence detection [9]. GC-TOF-MS is one of the best methods for direct determination although it is not cost-effective; further, these compounds are difficult to ionize.…”
Section: Introductionmentioning
confidence: 99%